Remote Laboratory for Measuring Linear Dimensions in the Process of E-Learning - Šulc, Jovan; Šešlija, Dragan; DudiÄ‡, Slobodan; Milenkovic, Ivana (International Journal of Online and Biomedical Engineering (iJOE), 2016)
Remote Laboratory for Measuring Linear Dimensions with remote access and control via Internet is developed and described in this paper. The system is realized at the University of Novi Sad, Faculty of Technical Sciences. This lab is dedicated to the students of secondary vocational schools and faculties with the aim to gain knowledge regarding linear dimension and mechanical component tolerance. Every user of this set-up is able to interact, observe and learn through the real measurement processes via communication infrastructure.